EGR1 and RXRA transcription factors link TGF-β pathway and CCL2 expression in triple negative breast cancer cells - Alisa M. Gorbacheva (Nature Portfolio, 2021)
Abstract Transforming growth factor beta (TGF-β) is the main cytokine responsible for the induction of the epithelial-mesenchymal transition of breast cancer cells, which is a hallmark of tumor transformation to the metastatic phenotype. Recently, research demonstrated that the chemokine CCL2 gene expression level directly correlates with the TGF-β activity in breast cancer patients. CCL2 attracts tumor-associated macrophages and is, therefore, considered as an important inductor of breast cancer progression; however, the precise mechanisms underlying its regulation by TGF-β are unknown. Here, we studied the behavior of the CCL2 gene in MDA-MB-231 and HCC1937 breast cancer cells representing mesenchymal-like phenotype activated by TGF-β. Using bioinformatics, deletion screening and point mutagenesis, we identified binding sites in the CCL2 promoter and candidate transcription factors responsible for its regulation by TGF-β. Among these factors, only the knock-down of EGR1 and RXRA made CCL2 promoter activity independent of TGF-β. These factors also demonstrated binding to the CCL2 promoter in a TGF-β-dependent manner in a chromatin immunoprecipitation assay, and point mutations in the EGR1 and RXRA binding sites totally abolished the effect of TGF-β. Our results highlight the key role of EGR1 and RXRA transcription factors in the regulation of CCL2 gene in response to TGF-β pathway.